Koreksi prospektif teks 2 Samuel 24 terhadap perilaku Daud bagi rekonstruksi kebijakan publik yang akuntabel - Gumulya Djuharto (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
This article offers another solution from the various solutions that have been offered previously to the problem in 2 Samuel 24 which is more disjunctive rather than conjunctive. In fact, conjunctive understanding using the public theology perspective of Paul Hanson which is analyzed by Oliver Glanz??